FLUID ISLAMIC IDENTITIES AND POSTHUMAN ASSEMBLAGES IN BANU MUSHTAQ’S HEART LAMP - Anjarsari, Fitrilya; Istiningdias, Dini Sri; Arlamanda Asri, Zietha; Rifai, Maulana (Balai Penelitian dan Pengembangan Agama Makassar, 2025)
This article reframes debates on Muslim women’s piety by moving from essences to practices that materialize at thresholds. Taking the short-story collection Heart Lamp as an analytic site, it proposes an “interface ethics” that reads piety as embodied coordination across veil–gate–movement. A diffractive close reading aligns posthuman feminism with Islamic feminist hermeneutics to map domestic ecologies, school-gate encounters, bus rides, humor as de-escalation, and multilingual drift as instances where agency is distributed across bodies, garments, objects, and spaces. This study identifies three significant findings: first, domestic scenes disclose micropolitics of piety that recalibrate authority through care work, timing, and spatial tact rather than doctrinal dispute. Second, material thresholds—corridors, ticket lines, doorways—assemble pious comportment as relational, iterative, and auditable in the text, shifting analysis from moral judgment to situated coordination. Third, accented translation sustains a polyvocal, posthuman voice: local Islamic registers remain audible while critique travels, preventing flattening into secular feminist or pietist monologues. These insights offer a portable heuristic for literary criticism and policy discourse: attend to interfaces, not identities. The study clarifies hijab controversies beyond binary moral panics, and suggests design implications for school-gate protocols, uniform guidelines, and queue management that minimize coercion while supporting dignity. It also outlines methodological audit trails—scene matrices linking indicators, quotations, and claims—that render hermeneutic reasoning transparent. The contribution is conceptual (interface ethics), empirical (text-grounded mappings), and practical (design heuristics). Centered on Heart Lamp’s South Asian Muslim milieux, the framework generalizes to comparable literatures and arenas, offering prompts for gate design, translation pedagogy, and dignity-forward regulation.